Pulse wave propagation along human aorta: a model study - Kizilova, N. N.; Mizerski, J. K.; Solovyova (Philippova), H. N. (My University, 2020)
In the study, wave propagation along aorta is studied for different normal and pathological conditions in distal arteries. The mathematical model is based on the axisymmetric incompressible Navier-Stokes equations for blood and momentum equations for an incompressible viscoelastic arterial wall. The solution has been found as a superposition of forward and backward running waves. The blood pressure and flow curves measured by ultrasound in larger systemic arteries of ten healthy volunteers have been used for identification of the model parameters. It is shown that individual geometry plays an essential role in the location of positive and negative wave reflection sites along the aorta and, thus, in the pressure and flow patterns as well as blood distribution into the side branches. The model is validated by comparative study with the same dependencies computed previously on a 55-tube model as well as on the measurement data. The model can be used for determination of the individual parameters for patient-specific cardiovascular models and further in silico modeling of the outcomes of surgical and therapeutic procedures.
Keywords: applied mechanics; biomechanics; waves in fluids; wave reflection; medical diagnostics